Is birth weight associated with risk of depressive symptoms in young women? Evidence from the Southampton Women's Survey. - Inskip, H; Dunn, N; Godfrey, K; Cooper, C; Kendrick, T (2008)
Although some studies have shown negative associations between birth weight and risk of depression, others have not. Studies also differ regarding the age and gender specificity of reported associations. In this paper, the authors report on a study of 5,830 women aged 20-34 years from the general population in Southampton, United Kingdom, interviewed in 2000-2002 that found no relation between birth weight and current depressive symptoms or past treatment for depression. Prevalence ratios for current symptoms and for past treatment, in relation to reported or recorded birth weights, were all remarkably close to 1.0, with narrow 95% confidence intervals. For example, the prevalence ratio from the fully adjusted model for current depressive symptoms in relation to a standard deviation increase in reported birth weight was 1.01 (95% confidence interval: 0.98, 1.05). Generally, the associations reported elsewhere are not strong. The authors found a weak, inverse association in exploratory analyses of duration of gestation at birth in relation to depressive symptoms, but this finding requires replication. Because birth weight and duration of gestation are relatively poor markers of fetal development, other markers of fetal and early development should be explored. However, data from this study do not support a major developmental contribution to the etiology of depression in women.